ADSORPTION EQUILIBRIUM STUDIES OF URANIUM (VI) ONTO CROSS-LINKED CHITOSAN-CITRIC ACID - HO , THI YEU LY; NGUYEN , VAN SUC; VO , QUANG MAI; NGUYEN , MONG SINH (Nuclear Science and Technology, 2012)
Investigation of U(VI) adsorption by the cross- linked chitosan with citric acid was conduced by bath method. Effect of parameters such as pH, contact time, adsorbent dosage and other metal cations was determined. The maximum adsorption capacity of U(VI) at pH 4 was found to be 243.90 mg U(VI)/g cross-linked chitosan - citric acid after 300 min of contact time. The Langmuir and Freundlich isotherm models were used to describe adsorption equilibrium. The correction values, R2 of two models were found to be 0.993 and 0.989, respectively. Therefore, it could be concluded that the adsorption equilibrium for U(VI) was followed the Langmuir and the Freundlich isotherm models.